2010
DOI: 10.4102/jsava.v81i2.114
|View full text |Cite
|
Sign up to set email alerts
|

A study of preslaughter pig handling and stunning in selected South African Highveld Region abattoirs

Abstract: The study hypothesis was that pre-slaughter handling is not conducted in such a way that pigs can be considered humanely slaughtered, nor is it conducive to promoting those properties of fresh meat that could enhance pork quality. The 1st phase of the investigation was aimed at confirming the present compliance level within the prescribed norms. To this end the importance of stunning induction requirements for effective electrical stunning, the welfare implications relating to the pre-slaughter handling of pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Various studies have shown that up to 13% of pigs required more than a single sticking attempt to bleed out properly (Anil et al, 2000;Spencer and Veary, 2010), This hazard can lead to recovery of consciousness. There are no published data concerning this hazard.…”
Section: Signs Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that up to 13% of pigs required more than a single sticking attempt to bleed out properly (Anil et al, 2000;Spencer and Veary, 2010), This hazard can lead to recovery of consciousness. There are no published data concerning this hazard.…”
Section: Signs Of Deathmentioning
confidence: 99%
“…Various studies have shown that up to 13% of pigs required more than a single sticking attempt to bleed out properly (Anil et al., ; Spencer and Veary, ),…”
Section: Assessmentmentioning
confidence: 99%
“…The effect of pre-slaughter handling on ultimate meat quality of pigs has been widely researched and reported on 3,6,10,15,17,21,23,25,26 . Pre-slaughter handling (time of last feeding, transport, lairage, stunning) affects meat quality by influencing both the rate and the extent of acidification of the muscles post mortem.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, very little work has been conducted on the effect of transport conditions and lairage time on pork quality. An investigation of 6 abattoirs in the Highveld Region in South Africa noted that there were marked differences in vehicle design and road conditions during the transport of the pigs 26 . It was also noted that the various abattoirs had no fixed rule regarding lairage holding time 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation